The New Orleans Alcohol Use in HIV Study: Launching a Translational Investigation of the Interaction of Alcohol Use with Biological and Socioenvironmental Risk Factors for Multimorbidity in People Living with HIV. (10th March 2019) - Welsh, David A.; Ferguson, Tekeda; Theall, Katherine P.; Simon, Liz; Amedee, Angela; Siggins, Robert W.; Nelson, Steve; Brashear, Meghan; Mercante, Donald; Molina, Patricia E.
Abstract : Background: Alcohol use disorders (AUDs) are highly prevalent in people living with HIV (PLWH) and are associated with increased HIV risk behaviors, suboptimal treatment adherence, potential interaction with medication pharmacodynamics, and greater risk for disease progression. Preclinical studies show that chronic binge alcohol administration accelerates disease progression and aggravates pathogenesis in the simian immunodeficiency virus (SIV)‐infected rhesus macaque model despite viral suppression by antiretroviral therapy. Methods: To translate preclinical findings in the rhesus macaque model of chronic binge alcohol administration and SIV infection and to address areas of uncertainty surrounding the biological mechanisms and socioenvironmental modifiers that contribute to the relationship between alcohol use and HIV‐associated comorbidities, precocious aging, and disease progression, we designed a translational multiproject, longitudinal, cohort study, and the New Orleans Alcohol Use in HIV ( NOAH ) Study . The NOAH Study is led by a multidisciplinary team of scientists, with a research focus on the interaction of AUD and HIV. The overarching hypothesis is that alcohol use will lead to adverse health outcomes in PLWH. In this report, we describe the study design and baseline descriptive characteristics of our cohort. Results: Three‐hundred and sixty‐five participants completed the baseline testing. The cohort is predominantly male (69%) and African American (83.5%). The majority of participants report incomes below 200% of the federal poverty level. CD4 counts <200 cells/ μ l were found in 12.8% and viral loads <50 copies/ml were found in 73.6%. These HIV status variables did not differ based upon alcohol use. Conclusions: The NOAH Study facilitates bidirectional translational investigation of alcohol's impact on PLWH. Translation of preclinical findings to PLWH permits confirmation of basic biological mechanisms in humans and also allows incorporation of sociobehavioral factors that may affect biology but are challenging to replicate in preclinical models. Abstract : The NOAH Study is led by a multidisciplinary team of scientists at LSUHSC, with a research focus on the interaction of AUD, HIV, and cART. This clinical study translates preclinical findings in the rhesus macaque model of chronic binge alcohol administration and SIV infection and facilitates bidirectional translational investigation of alcohol's impact on PLWH. Studies address areas of uncertainty surrounding the biological mechanisms and socioenvironmental modifiers that contribute to the relationship between alcohol use and HIV‐associated comorbidities, precocious aging, and disease progression.